Cardiac dysfunction in a cohort of biopsy proven nonalcoholic steatohepatitis in comparison to nonalcoholic fatty liver - Jijo Varghese; Krishnadas Devadas; Neeraj Vinayakumar; Nibin Nahaz; Atul Hareendran; Tharun Tom Oommen; Bony George (Egyptian Liver Journal, 2023)
Abstract Introduction NAFLD (non-alcoholic fatty liver disease) is increasing worldwide. Inflammation, fibrosis, and steatosis are the three components of NAFLD. Cardiac events are the most common cause of death in NAFLD. It is believed that there is an association between the inflammatory component of NAFLD and cardiac dysfunction. The gold standard for diagnosis of NAFLD is liver biopsy. Based on histology, NAFLD is categorized into two, nonalcoholic fatty liver (NAFL) and nonalcoholic steatohepatitis (NASH). As biopsy is an invasive procedure, studies comparing cardiac dysfunction in NAFL and NASH are few. The aim of our study is to compare cardiac dysfunction in patients with NAFL and NASH. Materials and method This is a cross-sectional study in which all patients who were biopsy proven for NAFLD without stage 4 fibrosis were included. Cardiac dysfunction in these patients was assessed by 2 D ECHO. Results Out of the 92 patients, 52 were males and 40 were females (53.5 vs 46.5 %). Among these patients, 48 had NAFL, whereas 48 had NASH. Among the variables analyzed for the study SGOT, SGPT, ALP, Ferritin, ANA, TSH, LVEF, LA diameter, E/e, NAS score, lobular inflammation, ballooning, and steatosis statistically correlated with cardiac diastolic dysfunction. Majority of the patients with NASH had cardiac dysfunction (32/44) while only a few patients with NAFL (4/48) had cardiac dysfunction (p value = 0.002). Among the variables that can cause diastolic dysfunction, i.e., coronary artery disease, dyslipidemia, diabetes mellitus, and hypertension, only diabetes mellitus had an independent association. By binary logistic regression, it was seen that NASH was an independent risk factor for predicting cardiac dysfunction. Conclusion The prevalence of cardiac dysfunction is more in NASH than NAFL in patients with NAFLD. NASH is an independent risk factor for cardiac dysfunction. There is no correlation between fibrosis and diastolic dysfunction.